Assessing the accessibility of HIV care packages among tuberculosis patients in the Northwest Region, Cameroon - Miguel San; Njozing Nwarbébé; Tih Pius; Hurtig Anna-Karin (BMC, 2010)
Abstract Background Tuberculosis (TB) and human immunodeficiency virus (HIV) co-infection is a major source of morbidity and mortality globally. The World Health Organization (WHO) has recommended that HIV counselling and testing be offered routinely to TB patients in order to increase access to HIV care packages. We assessed the uptake of provider-initiated testing and counselling (PITC), antiretroviral (ART) and co-trimoxazole preventive therapies (CPT) among TB patients in the Northwest Region, Cameroon. Methods A retrospective cohort study using TB registers in 4 TB/HIV treatment centres (1 public and 3 faith-based) for patients diagnosed with TB between January 2006 and December 2007 to identify predictors of the outcomes; HIV testing/serostatus, ART and CPT enrolment and factors that influenced their enrolment between public and faith-based hospitals. Results A total of 2270 TB patients were registered and offered pre-HIV test counselling; 2150 (94.7%) accepted the offer of a test. The rate of acceptance was significantly higher among patients in the public hospital compared to those in the faith-based hospitals (crude OR 1.97; 95% CI 1.33 - 2.92) and (adjusted OR 1.92; 95% CI 1.24 - 2.97). HIV prevalence was 68.5% (1473/2150). Independent predictors of HIV-seropositivity emerged as: females, age groups 15-29, 30-44 and 45-59 years, rural residence, previously treated TB and smear-negative pulmonary TB. ART uptake was 50.3% (614/1220) with 17.2% (253/1473) of missing records. Independent predictors of ART uptake were: previously treated TB and extra pulmonary TB. Finally, CPT uptake was 47.0% (524/1114) with 24% (590/1114) of missing records. Independent predictors of CPT uptake were: faith-based hospitals and female sex. Conclusion PITC services are apparently well integrated into the TB programme as demonstrated by the high testing rate. The main challenges include improving access to ART and CPT among TB patients and proper reporting and monitoring of programme activities.